Nursing of a patient with headache and insomnia after subdural hematoma treated by auricular acupoint pressing combined with Fire-Dragon cupping therapy (耳穴压豆联合火龙罐治疗1例硬膜下血肿患者头痛和不寐的护理体会) - ZOU Qun (邹群); ZHANG Yushan (张玉善); LU Qiaoping (卢巧萍) (中西医结合护理)
This paper summarized the effect of auricular acupoint pressing combined with Fire-Dragon cupping therapy and nursing interventions on headache and insomnia in a patient with subdural hematoma. Based on routine care and syndrome differentiation, auricular acupoint pressing, Fire-Dragon cupping and Traditional Chinese Medicine diet guidance were carried out to relieve the headache and improve the sleep quality of the patient. (本文总结1例耳穴压豆联合火龙罐治疗硬膜下血肿患者头痛和不寐的护理经验。完善护理评估, 在常规护理基础上辨证施护, 采用耳穴贴压、火龙罐以及中药膳食指导等中医护理技术, 有效改善患者头痛和不寐症状, 提高患者睡眠质量。)